Menimbang Kembali Formulasi dan Pewilahan Tari serta Konsep Ketubuhan dalam Masyarakat Urban - F.X. - Widaryanto (LP2M ISBI Bandung, 2012)
ABSTRACTÂ There are two sides of the paradox associated with the problem of dance formulation and catego- rization that can not be regarded easily. On the one hand, dance is a phenomenon of complexity, in which the intertextuality will embody a complicated contextual phenomenon. On the other hand, the step of categorization has a nature which facilitates someone to observe the existing various phenom- ena in a similarity of properties that tend to lead to a simplification.The development of very fast-moving art is not often followed by adequate category and categori- zation for the purpose of the study. This paper attempts to restore awareness of the concept of corpo- reality with the reality of the complexity, and reconsider and formulate the dance categorization in a creative tradition occured in Urban communities in Bandung in the period of 2000 to 2011.Â Keywords: corporeality, complexity, categorization, and dance.